2022
DOI: 10.36502/2022/asjbccr.6268
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Presentation of SMA Vasculitis with Chest and Upper Back Pain: Case Report

Abstract: Mesenteric ischemia is a phenomenon that occurs when arteries supplying the gastrointestinal tract either become narrowed or obstructed, thus reducing or halting downstream perfusion. This case study will explore a case of mesenteric ischemia caused by SMA vasculitis, a nonatherosclerotic abdominal arterial vasculopathy (NAV), in which a 57 y/o woman with history of hyperlipidemia and GERD presented to the ER with chest and upper back pain. Initial work up for MI and PE were inconclusive and the patient was di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
0
0
Order By: Relevance
“…One theory suggests that local exposure to antigens or infectious agents may lead to a local immune response. Other recent reports have found that viral infections, like COVID-19, may trigger inflammatory processes that could contribute to mesenteric vasculitis [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…One theory suggests that local exposure to antigens or infectious agents may lead to a local immune response. Other recent reports have found that viral infections, like COVID-19, may trigger inflammatory processes that could contribute to mesenteric vasculitis [ 5 ].…”
Section: Discussionmentioning
confidence: 99%